Flagging standards : globalization and environmental, safety, and labor regulations at sea - DeSombre, Elizabeth R. (MIT Press, 2006)
Examines the relationship between globalization and environmental, safety, and labor standards in the context of the shipping industry and explores the extent to which international competition affects regulatory standards.